Cementing material, cement mortar and cement mortar part
By using rice husk ash and calcined shell powder in the cementitious material partially replace cement, the problem of large energy consumption and low performance of existing cement-based materials is solved, and the development of high-performance cementitious materials is realized, with energy saving and environmental protection and Features of excellent mechanical properties.
Patent Information
- Application Number
- CN202411738201.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-14
AI Technical Summary
The existing cement-based materials have shortcomings in resource and energy consumption and performance, and it is difficult to take into account the requirements of high performance and energy conservation and environmental protection.
By using rice husk ash and calcined shell powder in the gelling material, it can be used as auxiliary gelling materials to reduce the amount of cement and improve the performance of the gelling material. Rice husk ash contains amorphous silica, and calcined shell powder contains calcium oxide, which can produce a variety of calcium silicate gel components in the hydration reaction, improving compressive strength and durability.
It has achieved the reduction of resource and energy consumption and reduced environmental impact, and at the same time, it has improved the compressive strength, anti-chlorine ion penetration, anti-sulfate corrosion resistance of cement mortar parts, and excellent durability.
Smart Images

Figure CN119430807A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of inorganic non-metallic materials, and in particular to cementitious materials, cement mortar, and cement mortar products. Background Art
[0002] Industries such as construction and civil engineering often require a large amount of cement and other cementitious materials. However, cement production requires long-term high-temperature calcination, so carbon emissions and energy consumption are very high. According to relevant research data, the process of producing one ton of cement will emit about 850 kilograms of carbon dioxide, consume 115 kilograms of standard coal, and emit a large amount of particulate matter. In the context of energy conservation and environmental protection, people have been studying the use of other cementitious materials to replace cement or partially replace cement. It is common to add auxiliary cementitious materials, but the replacement rate of auxiliary cementitious materials for cement is not high. A small amount of auxiliary cementitious materials when preparing cement mortar is beneficial to improve the performance of cement mortar, but if the amount of auxiliary cementitious materials is too high, it is easy to cause a decrease in mechanical properties such as compressive strength.
[0003] When cement is used in building materials, it is mainly the gelling components in cement that are mixed with water to form a slurry and undergo a hydration reaction, and finally the slurry solidifies to form a product. Mortar prepared only with cement often does not meet the requirements of industries such as construction and civil engineering. Therefore, in addition to auxiliary gelling materials, people also add other types of functional materials to obtain various cement-based materials when preparing cement mortar to improve the performance of cement-based cement mortar, hoping to increase the rate of hydration reaction, the workability of preparing slurry, and the mechanical properties such as compressive strength of the obtained products, resistance to chloride ion penetration, resistance to sulfate ion erosion, frost resistance, durability and other properties. However, existing cement-based materials are difficult to take into account the above effects or the improvement effect is limited.
[0004] Therefore, a high-performance cementitious material that saves resources and energy is needed. Summary of the invention
[0005] The purpose of the present application is to provide cementitious materials, cement mortar, and cement mortar products, aiming to solve the technical problems in the prior art of high resource and energy consumption and low performance of cement-based materials.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a gelling material, comprising the following components in parts by weight:
[0008] 5-20 parts of rice husk ash;
[0009] 5-20 parts of calcined shell powder;
[0010] 60-90 parts of cement;
[0011] Among them, rice husk ash contains amorphous silicon dioxide.
[0012] The cementitious material of the present application uses rice husk ash and calcined shell powder as auxiliary cementitious materials, and partially replaces cement, so that the amount of cement in the cementitious material is greatly reduced, the consumption of resources and energy is reduced, and the impact on the environment is reduced. At the same time, the raw materials of rice husk ash and calcined shell powder are waste from agricultural planting and fishery breeding respectively. The use of these two materials in the cementitious material can not only make full use of renewable resources, but also reduce the cost of waste treatment and realize resource utilization. In addition, when the cementitious material is subsequently mixed with water, on the one hand, the rice husk ash contains amorphous silicon dioxide (amorphous silicon dioxide) and has volcanic ash activity, and the calcined shell powder contains calcium oxide, which generates calcium hydroxide when it comes into contact with water, and can undergo a volcanic ash reaction with the rice husk ash to generate a variety of calcium silicate-type cementitious components, which is beneficial to improve the mechanical strength such as the compressive strength after hardening, and is also beneficial to filling the pores to increase the density and durability; on the other hand, the calcined shell powder is beneficial to increase the pH value of the slurry, provide a high alkalinity and high hydroxide ion environment, increase the volcanic ash activity of the rice husk ash, and promote the formation of cementitious components; on the other hand, both rice husk ash and calcined shell powder can fill the pores, and provide more nucleation sites for the hydration products of cement, thereby accelerating the hydration reaction.
[0013] In a second aspect, the present application provides a cement mortar, which is prepared by mixing the cementitious material of the above-mentioned application with water.
[0014] Since the above cementitious materials are rice husk ash and calcined shell powder that partially replace cement, rice husk ash is rich in amorphous silicon dioxide, and calcined shell powder is rich in calcium oxide, after being mixed with water, hydration reaction and volcanic ash reaction will be carried out to generate a large amount of calcium silicate cementitious materials to fill the pores in the cement mortar; at the same time, these rice husk ash and calcined shell powder can also fill the pores and provide more nucleation sites for the hydration products, accelerating the hydration reaction. Therefore, the obtained cement mortar has high mechanical properties such as compressive strength after the parts are made, and also has high resistance to chloride ion penetration and sulfate erosion, and excellent durability.
[0015] In a third aspect, the present application provides a cement mortar component, which is obtained by curing the cement mortar of the above application after molding.
[0016] The cement mortar of the present application is cured after being formed, so that the formed mortar gradually hardens during the curing process. The finally obtained cement mortar products have extremely high compressive strength, as well as high resistance to chloride ion penetration and sulfate erosion, and good durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 is the XRD pattern of rice husk ash in Example A1;
[0019] Figure 2 is the XRD pattern of the calcined shell powder in Example A1;
[0020] Figure 3 is a SEM image of the 7-day-cured cement mortar product of Example B5;
[0021] Figure 4 is a SEM image of the cement mortar product cured for 28 days in Example B5;
[0022] Figure 5 is a SEM image of the 7-day-cured cement mortar product of Example B8;
[0023] Figure 6 is a SEM image of the cement mortar product cured for 28 days in Example B8;
[0024] Figure 7 These are the XRD qualitative and quantitative graphs of the 7-day-cured cement mortar products of Examples B4, B5, B6, and Comparative Example B1;
[0025] Figure 8 These are the XRD qualitative and quantitative graphs of the 28-day-cured cement mortar products of Examples B4, B5, B6, and Comparative Example B1;
[0026] Fig. 9 is a top view of the cement mortar parts of Examples B1 and B10;
[0027] Fig.10 It is a side view of the cement mortar parts of Examples B1 and B10. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0030] In this application, "at least one" means one or more, "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items.
[0031] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0032] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0033] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0034] In a first aspect, an embodiment of the present application provides a gelling material, comprising the following components in parts by weight:
[0035] 5-20 parts of rice husk ash;
[0036] 5-20 parts of calcined shell powder;
[0037] 60-90 parts of cement;
[0038] Among them, rice husk ash contains amorphous silicon dioxide.
[0039] The cementitious material of the embodiment of the present application uses rice husk ash and calcined shell powder as auxiliary cementitious materials, and partially replaces cement, so that the amount of cement in the cementitious material is greatly reduced, the consumption of resources and energy is reduced, and the impact on the environment is reduced. At the same time, the raw materials of rice husk ash and calcined shell powder are waste from agricultural planting and fishery breeding, respectively. The use of these two materials in the cementitious material can not only make full use of renewable resources, but also reduce the cost of waste treatment, and realize resource utilization. In addition, when the cementitious material is subsequently mixed with water, on the one hand, the rice husk ash contains amorphous silicon dioxide (amorphous silicon dioxide) and has volcanic ash activity, and the calcined shell powder contains calcium oxide, which generates calcium hydroxide when it comes into contact with water, and can undergo a volcanic ash reaction with the rice husk ash to generate a variety of calcium silicate-type cementitious components, which is beneficial to improve the mechanical strength such as the compressive strength after hardening, and is also beneficial to filling the pores to increase the density and durability; on the other hand, the calcined shell powder is beneficial to increase the pH value of the slurry, provide a high alkalinity and high hydroxide ion environment, increase the volcanic ash activity of the rice husk ash, and promote the formation of cementitious components; on the other hand, both rice husk ash and calcined shell powder can fill the pores, and provide more nucleation sites for the hydration products of cement, thereby accelerating the hydration reaction.
[0040] In addition, the mass fractions of rice husk ash and calcined shell powder in the cementitious material in the embodiment of the present application need to meet the above range, and when mixed with water, the volcanic ash reaction and the filling effect can be taken into account, so that the product can take into account various properties. If the amount of rice husk ash and calcined shell powder replacing cement is too high, although energy consumption is reduced and resource utilization is beneficial, the filling effect is reduced, resulting in loose gel components; it also weakens the alkaline excitation effect of cement and reduces the activity of rice husk ash. The particle accumulation and slow reaction will eventually affect the growth of mechanical properties such as compressive strength.
[0041] [About rice husk ash]
[0042] Rice husk ash is referred to as RHA. Rice husk is a by-product of rice production. The main components of rice husk are silicon-containing substances such as cellulose, lignin, and silica. It also includes lower levels of lipids, proteins and other substances. Only a small part of the large amount of rice husks in agricultural production is reasonably utilized, mainly for brewing, vinegar making, feed production and as fuel. After calcination under aerobic conditions, organic matter will generate carbon dioxide, water vapor, etc., and the solid residue left is rice husk ash. The yield is about 20% of the mass of rice husk before combustion, and the relative density is about 2.14, which is lower than the density of traditional cement and slag powder. Due to the porosity of rice husk, the calcined rice husk ash has a large specific surface area, usually 50-100m 2 / g.
[0043] The main component of rice husk ash is silicon dioxide. Depending on the raw materials and sintering process, the content of silicon dioxide in rice husk ash is usually between 87% and 97%. Silicon dioxide can be amorphous silicon dioxide (amorphous silicon dioxide) or crystalline silicon dioxide. Among them, crystalline silicon dioxide is relatively stable and basically has no volcanic ash activity and cannot react with components such as calcium hydroxide; amorphous silicon dioxide has volcanic ash activity, similar to silica fume, and can react with calcium hydroxide and other components through secondary hydration reaction with cement-based materials to improve the performance of the obtained cement mortar.
[0044] Therefore, the effectiveness of the pozzolanic reaction is closely related to the content and crystallinity of silica in rice husk ash. The presence of crystalline or semi-crystalline silica significantly affects the reaction with cement, calcined shell powder, and water. The crystallinity of silica in rice husk ash is closely related to the calcination temperature, and the temperature needs to be strictly controlled. If the time and temperature are not properly controlled, such as the temperature is too low and the time is too short, it may cause a large amount of unburned carbon in the rice husk ash. If the temperature is too high, a large amount of crystalline silica will be generated, which will have an adverse effect on the strength of the cementitious material when it is used. When the calcination temperature is between 500°C and 800°C, the calcination process will form a large amount of amorphous silica. When the calcination temperature exceeds 800°C, silica gradually changes from an amorphous state to a crystalline phase, and begins to generate crystalline silica, such as quartz, thereby reducing the pozzolanic properties of rice husk ash.
[0045] Therefore, in order to obtain highly active rice husk ash, the calcination temperature of rice husk must be strictly controlled. When the combustion temperature is between 500°C and 800°C, the volcanic ash activity of rice husk ash is the highest. In some embodiments, rice husk ash is made by calcining rice husk at 500-1000°C, which can be 500-800°C. In the exemplary embodiment, it can include but is not limited to any value of 500°C, 600°C, 700°C, 800°C, 1000°C or any range between two values. The calcination time can be 3-4h. After testing and controlling the appropriate reaction conditions, the mass ratio of silicon dioxide to rice husk ash is about 93%, of which the mass ratio of amorphous silicon dioxide to rice husk ash can be 82%-86%.
[0046] In addition to amorphous silica, the particles and gradation of rice husk ash will also affect the performance of cementitious materials. The size of the particles will directly affect the bonding state of rice husk ash and cement. The finer the rice husk ash particles, the stronger the reactivity. The larger rice husk ash particles are mostly crystalline and mainly serve as pore fillers, and rarely undergo pozzolanic reactions. Moreover, if the rice husk ash particles obtained by calcination are not ground, they will generally be irregular, bubbly, layered and porous in appearance, resulting in a high porosity of the mortar after the cementitious material and water are mixed, thereby reducing the compressive strength and durability. Therefore, the rice husk ash obtained by calcination can be ground and screened to make the rice husk ash show excellent chemical activity and fine particle filling effect. In some embodiments, the particle size of the rice husk ash is through a 300-mesh sieve to improve the above-mentioned properties. Optionally, the Dv10 particle size of the rice husk ash is 0.63-1.03 μm, the Dv50 particle size is 4.91-5.31 μm, and the Dv90 particle size is 8.47-8.87 μm.
[0047] Finally, rice husk ash plays an important role in workability and fluidity during early curing when mixing cementitious materials with water. The irregular and porous particle morphology enhances the water retention capacity and reduces the lubricity of the paste. In the hardened state, rice husk ash particles act as microfillers, increasing the density of the cement mortar and reducing the porosity. In the medium- and long-term hydration process, rice husk ash acts as a raw material for pozzolanic reactions to form calcium silicate-based gels, thereby improving the compressive strength of the cement mortar. Due to its small particle size, rice husk ash also provides more nucleation sites for hydration products, accelerating the hydration of cement clinker.
[0048] It can be seen that the application of rice husk ash can improve the basic mechanical properties and microstructure of cement mortar, reduce resource and energy consumption, reduce the impact on the environment, and promote the green development of the cement industry. It also reduces the cost of waste treatment and realizes resource utilization.
[0049] [About calcined shell powder]
[0050] Calcined shell powder is referred to as CSP. Shells are the protective shells of shellfish and are a by-product of aquaculture. Shellfish are often eaten as food, while most of the inedible shells are discarded. About 10 million tons of discarded shellfish are landfilled every year, and only a small part is reused for other purposes, such as fertilizers and handicrafts. The secondary use of shells is limited by many factors, including the lack of soil solidification technology, economic cost considerations, and market demand for recycled products. If discarded shells are not processed for a long time, the meat remaining in the shells will oxidize and rot, and microorganisms will decompose salt into harmful gases, such as H2S and NH3, producing a foul odor and causing environmental pollution problems.
[0051] Shells are rich in calcium carbonate, which can be converted into calcium oxide after calcination, so calcined shell powder contains a large amount of calcium oxide. In some embodiments, calcined shell powder is obtained by calcining shells at 800-1000°C and then grinding. The calcination temperature can be selected to be ≥1000°C, and the mass proportion of calcium oxide in the obtained calcined shell powder is 95%-98%. Therefore, on the one hand, after the cementitious material and water are mixed, the calcined shell powder can effectively promote the hydration reaction of cement, which is conducive to the formation of hydration products, and generates calcium silicate gel, calcium hydroxide, etc., thereby improving the mechanical properties and durability of mortar; on the other hand, calcined shell powder can also cooperate with rice husk ash and water to react with volcanic ash to generate a large amount of calcium silicate gel, fill the pores of cement mortar to increase density, thereby improving compressive strength, and also enhancing its resistance to environmental factors, such as resistance to sulfate erosion, and improving durability; on the other hand, calcined shell powder is also conducive to increasing the pH value of the slurry, which is more conducive to the volcanic ash activity of rice husk ash. Finally, after the calcination treatment is completed, it can be ground and sieved to make the particle size of the calcined shell powder pass through a 325 mesh sieve. Optionally, the Dv10 particle size of the calcined shell powder is 2.56-2.96 μm, the Dv50 particle size is 7.74-8.14 μm, and the Dv90 particle size is 19.80-20.20 μm. The fine particles of the calcined shell powder with such a particle size help to fill the pores and improve the overall density and strength.
[0052] Therefore, the addition of calcined shell powder greatly improves the performance of cementitious materials, reduces the amount of cement, reduces resource and energy consumption, reduces the impact on the environment, and promotes the green development of the cement industry. It also reduces the cost of waste treatment, realizes resource utilization, and prevents shellfish waste from polluting the environment.
[0053] [About cement]
[0054] In some embodiments, the cement includes at least one of silicate cement and ordinary silicate cement. Ordinary silicate cement of grade 42.5 may be selected, such as 42.5R high early strength cement, and ordinary silicate cement of grade 52.5 may be selected. Optionally, the cement has a Dv10 particle size of 1.08 to 1.48 μm, a Dv50 particle size of 14.50 to 14.90 μm, and a Dv90 particle size of 44.60 to 45.00 μm.
[0055] [About the entire cementitious material]
[0056] Rice husk ash and calcined shell powder partially replace cement. In this way, after the cementitious material and water are mixed, in the early reaction, the cement hydration reaction and the reaction of calcined shell powder with water will generate a large amount of calcium hydroxide. In addition, the partial replacement of cement by calcined shell powder further increases the concentration of calcium ions, which is conducive to the formation of early reaction products such as calcium hydroxide. Since rice husk ash has a high volcanic ash reaction activity, it can consume the free calcium hydroxide in the cement mortar to produce a volcanic ash reaction (mainly occurring in the later stage of curing) and generate a calcium silicate gel component to fill the pores in the cement mortar. Rice husk ash particles and calcined shell powder also provide nucleation sites for the cement hydration reaction and the formation of hydration products, accelerating the hydration reaction of the cementitious material.
[0057] Replacing part of the cement with calcined shell powder can increase the pH value of the slurry obtained by mixing with water and increase the concentration of OH-. OH- ions can destroy the chemical bonds of amorphous silica in rice husk ash and accelerate the volcanic ash reaction, especially when the pH value exceeds 13.2, which is more conducive to the activity of rice husk ash.
[0058] Theoretically, the more rice husk ash is added, the more pozzolanic reaction products are generated. However, if the replacement level of rice husk ash increases to the extent that the alkaline activation effect of cement is weakened, the reactivity of rice husk ash may decrease, resulting in a slow reaction; and, the higher the addition amount, the lower the filling effect of fine particles, resulting in loose gel components. Slow reaction and particle accumulation will eventually affect the growth of mechanical properties such as compressive strength.
[0059] Therefore, the rice husk ash and calcined shell powder in the cementitious material can only partially replace cement, wherein the mass parts of each component can be 5 to 20 parts of rice husk ash, 5 to 20 parts of calcined shell powder, and 60 to 90 parts of cement. The mass parts of rice husk ash may include but are not limited to any value of 5, 10, 15, 20 parts or a range between any two values. The mass parts of calcined shell powder may include but are not limited to any value of 5, 10, 15, 20 parts or a range between any two values. The mass parts of cement may include but are not limited to any value of 60, 70, 80, 90 parts or a range between any two values. In the exemplary embodiment, the cementitious material can be obtained according to the ratio of 15 parts of rice husk ash, 10 parts of calcined shell powder, and 75 parts of cement.
[0060] A second aspect of an embodiment of the present application is a cement mortar, which is prepared by mixing the cementitious material of the embodiment of the present application with water.
[0061] Since the above cementitious materials are rice husk ash and calcined shell powder that partially replace cement, rice husk ash is rich in amorphous silicon dioxide, and calcined shell powder is rich in calcium oxide, after being mixed with water, hydration reaction and volcanic ash reaction will be carried out to generate a large amount of calcium silicate cementitious materials to fill the pores in the cement mortar; at the same time, these rice husk ash and calcined shell powder can also fill the pores and provide more nucleation sites for the hydration products, accelerating the hydration reaction. Therefore, the obtained cement mortar has high mechanical properties such as compressive strength after the parts are made, and also has high resistance to chloride ion penetration and sulfate erosion, and excellent durability.
[0062] In some embodiments, the mass ratio of cementitious material to water is 1:(0.18-0.35). In the exemplary examples, it may include but is not limited to any ratio of 1:0.18, 1:0.25, 1:0.3, 1:0.35 or a range between any two values. 1:0.3 may be selected. The mass ratio of cementitious material to water directly affects the hydration reaction rate of the cement mortar and the amount of cementitious components generated. It also affects the mixing uniformity, workability and other properties. A suitable water-cement ratio is conducive to the mortar having higher construction performance and mechanical properties.
[0063] In some embodiments, the mixing process may include the following steps: first, calcined shell powder and water are mixed into a mixed slurry and heat is released; then, rice husk ash, the mixed slurry, and cement are mixed. Since calcined shell powder is rich in calcium oxide, it will release a lot of heat when reacting with water to generate calcium hydroxide. If the above-mentioned cementitious material is directly mixed with water, a large number of bubbles will be generated, and the hydration reaction and the volcanic ash reaction will be affected. Finally, the obtained product is full of cracks and large pores, which will greatly affect the compressive strength and durability. Therefore, the calcined shell powder and water can be mixed into a mixed slurry to generate a large amount of calcium hydroxide, and then mixed with rice husk ash and cement after heat release, and the subsequent hydration reaction and volcanic ash reaction will be fully carried out to generate a large amount of cementitious components, and high-performance cement mortar can be obtained.
[0064] In some embodiments, the mixed raw materials also include at least one of aggregate, water reducer, and defoamer. Aggregate plays the role of skeleton and support in cement mortar, improves stability, reduces the porosity inside cement mortar, and improves compressive strength and durability. It can also reduce water consumption and reduce costs. Standard sand and other filling materials can be selected. The mass ratio of aggregate to cementitious material can be (1.5-1.8):1, and can be 1.6:1. The water reducer is conducive to dispersing cement particles, and can also improve workability and fluidity, reduce the amount of water, reduce the water-cement ratio, improve compressive strength, density and durability, and reduce slump loss. It can include a polycarboxylic acid-based high-efficiency water reducer, and the mass ratio of the water reducer to the cementitious material can be (0.32-0.42):1.
[0065] A third aspect of an embodiment of the present application provides a cement mortar component, which is obtained by curing the cement mortar of the above embodiment of the present application after molding.
[0066] The cement mortar in the embodiment of the present application is cured after being formed, so that the formed mortar gradually hardens during the curing process. The finally obtained cement mortar products have extremely high compressive strength, as well as high resistance to chloride ion penetration and sulfate erosion, and good durability.
[0067] The specific molding method is to mix the cement mortar evenly and pour it into the mold, and use a vibrating table to vibrate it evenly to remove pores and bubbles. Avoid high temperature and sunlight exposure during the process to prevent premature hardening. After molding, cover the surface with plastic film after initial solidification, stand for 24 hours and then remove the mold. Then cure it in 20±3℃ water, or cure it in an environment with a temperature of 20±3℃ and 100% humidity to allow the mortar to gradually harden. After the curing period of 7 days or 28 days, take it out to obtain a cement mortar product. Since the volcanic ash reaction mainly occurs in the later stage of curing, the curing time can be selected to be longer, and the optional curing time is 28 days.
[0068] The following describes the invention in conjunction with specific embodiments.
[0069] Example A1
[0070] This embodiment provides cement mortar and a preparation method thereof, the raw material ratio of which is recorded in Table 1, and the preparation method comprises the following steps:
[0071] S1: Rice husks are provided by Tianfu Granary in Dongpo District, Meishan City, Sichuan Province. The rice husks are first cleaned to remove impurities, and then the dried rice husks are placed in a muffle furnace. The temperature is raised at a rate of 5°C / min. When the temperature rises to 500°C, it is maintained for one hour, and then further raised to 800°C at the same rate and maintained for three hours. After the process is completed, the furnace is allowed to cool naturally. The cooked rice husks are then taken out for grinding, sieved using a 300-mesh sieve, and the sieved components are taken as rice husk ash (RHA).
[0072] S2: Oyster shells are provided by the oyster breeding base in Zhanjiang City, Guangdong Province. The washed and dried oyster shells are placed in a muffle furnace and heated to 1000°C at a rate of 10°C / min for three hours. After the program is completed, the shells are naturally cooled. A 325-mesh sieve is used for sieving, and the components under the sieve are taken as calcined shell powder (CSP).
[0073] S3: ISO standard sand was provided by Xiamen ISO Co., Ltd. and analyzed by LT2200E laser particle size analyzer of Zhuhai Zhenli Optical Instrument Co., Ltd. to obtain the solid particle size distribution curve. The average particle sizes of RHA, CSP, cement and standard sand were 5.12μm, 8.54μm, 14.25μm and 378.35μm respectively. Based on the particle size distribution characteristics of cement and standard sand, and in accordance with JGJ55-2010 "Ordinary Concrete Mix Design Code", the modified Andreasen and Andersen close packing model was used to design the mix proportion. The cementitious materials include 10 parts by mass of RHA, 5 parts by mass of CSP and 85 parts by mass of cement, and the proportion of cement partially replaced can be seen. When mixing, the water-cement mass ratio is 0.3:1, and the mass ratio of raw materials is kept as cementitious materials: standard sand: water = 1:1.6:0.3. The amount of water reducer is based on the slump of cement mortar maintained at 240mm, and the allowable deviation is within the range of ±5%. The water reducer used is a polycarboxylic acid high-performance water reducer provided by Shanghai Master Construction High-Tech Building Chemical Co., Ltd., which is light yellow and transparent, with a solid content of 24.7% and a pH value of 5.4; the cement is PO 42.5R high early strength cement provided by Sanhe Yanhong Trading Co., Ltd.
[0074] S4: CSP was mixed with laboratory tap water and allowed to stand for half an hour to complete the exothermic reaction to obtain a mixed slurry.
[0075] S5: Wipe the inner wall and blades of the mortar mixer with a wet rag to achieve a good cleaning and wetting effect. Then pour 42.5R high early strength cement, RHA and ISO standard sand into the mixer in turn, mix at low speed for 3 minutes to improve the uniformity of dry materials; then add the mixed slurry and stir at high speed for 3 minutes to obtain cement mortar. According to the ratio of RHA and CSP to partially replace cement, it is recorded as R10S5. The letter "R" in this mark represents RHA, "S" represents CSP, and the numbers after the letters represent the percentage of each material.
[0076] Example A2
[0077] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the amount of raw materials is different, and the other aspects are the same, and is denoted as R10S10.
[0078] Example A3
[0079] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the amount of raw materials is different, and the other aspects are the same, and is denoted as R10S15.
[0080] Example A4
[0081] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the amount of raw materials is different, and the other aspects are the same, and is denoted as R15S5.
[0082] Example A5
[0083] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the amount of raw materials is different, and the other aspects are the same, and is denoted as R15S10.
[0084] Example A6
[0085] This embodiment provides cement mortar and a preparation method thereof, which differs from Embodiment A1 only in that the amount of raw materials used is different, and the other aspects are the same, and is denoted as R15S15.
[0086] Example A7
[0087] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the amount of raw materials is different, and the other aspects are the same, and is denoted as R20S5.
[0088] Example A8
[0089] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the amount of raw materials is different, and the other aspects are the same, and is denoted as R20S10.
[0090] Embodiment A9
[0091] This embodiment provides cement mortar and a preparation method thereof, which differs from Embodiment A1 only in that the amount of raw materials used is different, and the other aspects are the same, and is denoted as R20S15.
[0092] Embodiment A10
[0093] This embodiment provides cement mortar and a preparation method thereof, which is different from Embodiment A1 only in that the step of mixing CSP with water to prepare a mixed slurry and releasing heat in Step S4 of Embodiment A1 is deleted, and CSP is directly mixed with dry materials in Step S5, and finally the dry materials are mixed with water, and the rest are the same.
[0094] Comparative Example A1
[0095] This comparative example provides cement mortar and a preparation method thereof, which differs from Example A1 only in that the amount of raw materials is different, and the others are the same, and is recorded as R0S0 as a blank control group.
[0096] Comparative Example A2
[0097] This comparative example provides cement mortar and a preparation method thereof, which is different from Example A1 only in that the temperature of 800° C. in step S1 is changed to 1200° C., and the rest are the same.
[0098] Comparative Example A3
[0099] This comparative example provides cement mortar and a preparation method thereof, which is different from Example A1 only in that the oyster shells in step S2 are not calcined but directly ground to obtain shell powder, and the rest are the same.
[0100] The differences between Examples A1 to A10 and Comparative Examples A1 to A3 are shown in Table 1. The units of the numbers below "cementitious material", "standard sand", "water" and "water reducing agent" in Table 1 are all parts by mass.
[0101] Table 1
[0102]
[0103] Cement mortar parts embodiment:
[0104] The cement mortars provided in the above-mentioned Examples A1 to A10 and Comparative Examples A1 to A3 were respectively used to prepare cement mortar products according to the following methods:
[0105] After the cement mortar is mixed, pour it into 100×100×100mm 3 Cube triple mold with 40×40×160mm 3 Place the specimen in a prism triple mold and vibrate on a vibration table for 50 seconds to evenly distribute the slurry. Use a spatula to smooth the cement mortar molding surface to prevent the uneven surface of the specimen from causing eccentric compression damage during the compressive strength test. Cover the specimen molding surface with plastic film after initial solidification, let it stand for 24 hours, then remove the mold, and then cure it in 20±3℃ water. After the 7-day and 28-day curing period, take it out for subsequent tests.
[0106] Among them, the cement mortar of Example A1 is used to prepare the cement mortar parts of Example B1, the cement mortar of Example A2 is used to prepare the cement mortar parts of Example B2, and so on, until the cement mortar of Comparative Example A3 is used to prepare the cement mortar parts of Comparative Example B3.
[0107] Related performance tests and result analysis
[0108] Raw material performance test
[0109] The RHA and CSP in Example A1 were analyzed, and the chemical compositions were analyzed by an ARL Perform X-ray fluorescence spectrometer (XRF) produced by Thermo Fisher Scientific, USA, and the results are recorded in Table 2. X-ray diffraction (X-Ray Diffraction, XRD) analysis was performed using a Bruker D8 Advance X-ray powder diffractometer produced by Bruker, Germany, and the XRD patterns of RHA and CSP were obtained. The results of RHA are shown in Table 2. Figure 1As shown, the results of CSP are as follows Figure 2 shown.
[0110] Table 2
[0111]
[0112] from Figure 1 From the XRD spectrum, it can be seen that RHA has a high amorphous content. The compounds in rice husk ash were analyzed, and it was found in Table 2 that the most abundant compound was SiO2, accounting for 93.15% of the total. This shows that the crystal content of burning rice husk ash can be kept low and the amorphous proportion can be kept high by controlling the temperature and combustion time, thus ensuring the volcanic ash activity.
[0113] from Figure 2 As can be seen from Table 2, CPS contains a large amount of CaO. Therefore, the CaO in the calcined shell powder can react quickly with water to form calcium hydroxide (CH).
[0114] Therefore, a volcanic ash reaction will occur between RHA, CSP and water, and the formed CSH gel can improve strength, fill voids and enhance durability.
[0115] Related tests on the performance of cement mortar products
[0116] 1 Mechanical properties test
[0117] Mechanical property tests were performed on the articles of Examples B1 to B10 and Comparative Examples B1 to B3, and the articles cured for 7 days and 28 days were tested. At least three samples were tested for each example or comparative example for each test, and the average value was taken.
[0118] 1.1 Compressive strength
[0119] The compressive strength test is carried out in accordance with the "Test Method for Cement Mortar Strength" (GB / T 17671-2021). The test is carried out using a UTM universal testing machine. During the test, the deviation between the center of the specimen and the center of the press should be kept within the range of ±0.5mm, and the loading rate should be 2400N / s±200N / s until the specimen is destroyed and the loading is stopped.
[0120] 1.2 Flexural strength
[0121] The flexural strength test is carried out in accordance with the "Test Method for Strength of Cement Mortar" (GB / T 17671-2021). During the test, the specimen is first placed under a 600kN SANS electronic universal testing machine, a constant loading rate of 50N / s is applied to the specimen, and the load at fracture is recorded.
[0122] 1.3 Splitting tensile strength
[0123] The splitting tensile strength test was carried out in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019). First, the specimen was placed under a 600kN SANS electronic universal testing machine, and then a constant loading rate of 0.5MPa / s was applied to the specimen, and the specimen failure load was recorded.
[0124] 1.4 Axial compressive strength
[0125] The axial compressive strength test was carried out in accordance with the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The specimen was placed under a 600kN SANS electronic universal testing machine, a constant loading rate of 0.5MPa / s was applied to the specimen, and the specimen failure load was recorded.
[0126] Some of the above test results are recorded in Table 3:
[0127] Table 3
[0128]
[0129] It can be seen from Table 1 and Table 3 that a certain amount of RHA and CSP replacing part of the cement can significantly improve the compressive strength of cement mortar, especially in the development of later strength. At 7 days of curing, due to the use of early high-strength cement, the 7-day compressive performance of comparative example B1 is relatively high, but with the curing to 28 days, the performance of RHA and CSP replacing part of the cement is significantly improved, indicating that the pozzolanic reaction mainly occurs in the later stage of curing. R15S10 showed the best mechanical properties at both curing ages, indicating that this ratio achieved the best balance between pozzolanic reaction and filler effect. The high reactivity of CSP and the filling effect of RHA make the cement mortar have good initial workability and fluidity, while the pozzolanic effect of RHA appears in the later stage, further improving the compressive strength. However, if the RHA dosage is too high (such as 20%), particle accumulation and slow reaction will occur, which will affect the growth of compressive strength.
[0130] 2 Micro performance test
[0131] 2.1 Scanning electron microscope test
[0132] Before testing, the sample needs to be prepared first. After the concrete stops hydration, select a block with a size not exceeding 5mm in height, extract the gas from the internal pores of the specimen under a vacuum environment, and spray the specimen with gold. After the specimen is prepared, place it on the observation table, adjust the parameters of the scanning electron microscope in the backscattered electron (BSE) mode to obtain a clear image, and observe the microscopic morphology of mortar concrete of each mix ratio under different temperatures and curing systems.
[0133] Among them, the SEM image of Example B5 after 7 days of curing is as follows: Figure 3 As shown, the SEM image of Example B5 after 28 days of curing is as follows Figure 4 The SEM image of Example B8 after 7 days of curing is shown in FIG. Figure 5 As shown, the SEM image of Example B5 after 28 days of curing is as follows Figure 6 shown.
[0134] 2.2 Porosity test
[0135] The mercury intrusion method can use mercury to test the pores of the workpiece. The pressure is gradually applied to the sample and the amount of mercury intrusion under different pressures is recorded. When under pressure, the smaller the pore, the greater the force required to intrude the mercury. By monitoring the amount of mercury intrusion under different pressures, the pore size and pore volume can be reflected. A mercury intrusion analyzer was used for pore structure testing. The mercury intrusion analyzer was an AutoPore Iv9510 high-performance fully automatic mercury intrusion analyzer. The porosity test results of the specimens cured for 28 days in each case are recorded in Table 4.
[0136] 2.3 X-ray diffraction analysis
[0137] Qualitative and quantitative analysis was performed using a Bruker AXSD8ADVANCE X-ray diffractometer and the Rietveld external standard method with a scanning angle of 3° to 80° and a scanning speed of 10° / min.
[0138] The test results of the specimens cured for 7 days in Example B4, Example B5, Example B6 and Comparative Example B1 are as follows: Figure 7 The test results of the specimens cured for 28 days in Example B4, Example B5, Example B6 and Comparative Example B1 are shown in FIG. Figure 8 shown.
[0139] 2.4 Thermogravimetric analysis
[0140] A German NETZSCH DSC3500 Sirius differential scanning calorimeter was used. The experimental temperature was 35-947°C and the heating rate was 10°C / min.
[0141] 3. Durability test
[0142] 3.1 Sulfate corrosion resistance dry-wet cycle test
[0143] Referring to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete GB / T50082-2009, a sulfate dry-wet cycle test was set up indoors. First, the specimens cured to 28 days old were taken out and placed in an oven at 80±5℃ for 48 hours. After the test, the specimens were placed in a dry environment and cooled to room temperature. The specimens were placed in a 5% Na2SO4 solution for a dry-wet cycle test. The dry-wet cycle period was 24±2h, of which the immersion time was 25±0.5h. After the immersion, the liquid was drained within 30 minutes and air-dried for 30 minutes. After the air-drying was completed, high-temperature treatment was immediately carried out at 80℃ for 6 hours. After the treatment was completed, the specimens were cooled to room temperature for 2 hours. At this point, a dry-wet cycle step was completed. The compressive strength of the specimens after different dry-wet cycles was tested using a universal testing machine to evaluate the sulfate corrosion resistance of the cement mortar. The ratio of the compressive strength after dry-wet cycles to the initial compressive strength is recorded in Table 4. The higher the strength ratio, the stronger the sulfate corrosion resistance.
[0144] 3.2 Antifreeze performance test
[0145] With reference to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete GB / T50082-2009, a sulfate freeze-thaw cycle test was set up indoors. First, after the specimens were cured for 24 days, they were taken out and immersed in water for 4 days. After that, the specimens were taken out and the moisture on the surface of the specimens was wiped off with a wet rag. Then, the specimens were placed in a freezer and the temperature of the freezer was lowered to -18°C within 1.5 to 2 hours. After the cooling was completed, the freezing time was not less than 4 hours. After the freezing was completed, the specimens were immersed in water at 18 to 20°C for 4 hours, and a freeze-thaw cycle was completed after the immersion was completed. The compressive strength of cement mortar parts with 50, 100 and 150 freeze-thaw cycles was tested using a UTM universal testing machine to evaluate the antifreeze performance of cement mortar parts. The strength loss rate of 150 freeze-thaw cycles is recorded in Table 4.
[0146] 3.3 Chloride ion penetration resistance test
[0147] With reference to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete GB / T50082-2009, the rapid chloride ion migration coefficient method (RCM method) was used to simulate the corrosion of chloride salt solution on cement mortar products. The test results of the specimens cured for 28 days are recorded in Table 4.
[0148] Table 4
[0149]
[0150]
[0151] Combining all the above tests, the results of thermogravimetric analysis show that the higher the CSP dosage, the more calcium hydroxide (CH) content in the cement mortar, while the addition of RHA will reduce the CH content with the increase of curing time. This is due to the progress of the pozzolanic reaction and the release of RHA activity under high pH conditions. The RHA dosage has a significant effect on the compressive strength and CH content of the cement mortar, especially in the later stage of curing, when the pozzolanic reaction consumes a large amount of CH to generate calcium silicate (CSH) gel, thereby improving the compressive strength of the cement mortar. R15S10 has the largest increase in dehydration peak and the least amount of CH remaining, which corresponds to its best mechanical properties. However, excessive RHA will cause the CSH gel to loosen and affect the strength performance.
[0152] The addition of CSP and RHA helps to reduce the total porosity and refine the pore structure. In particular, R15S10 performs best in improving the pore structure, with a significant reduction in total porosity and main pore size, indicating that the products generated by the volcanic ash reaction effectively fill the pores and improve the density of the cement mortar. The addition of CSP not only enhances the volcanic ash activity of RHA, but also promotes the formation of high-density CSH gel, further refines the pores, and enhances the comprehensive performance of the cement matrix. However, when the RHA dosage is too high, the total porosity and main pore size of the cement mortar increase, the degree of pore structure refinement weakens, and the compressive strength decreases.
[0153] The formation of microcracks and pores is mainly concentrated in the transition zone between aggregate and cement paste interface, which is particularly obvious in the early stage (7 days), mainly due to the slow reaction of pozzolanic ash and the water absorption characteristics of RHA particles. However, with the extension of curing time (to 28 days), RHA gradually dissolves and generates a large amount of CSH gel to fill the pores, which significantly improves the density and compressive strength of cement mortar. Samples with different proportions show similar trends. The porosity is higher at the early age, and there are more unhydrated cement particles. As time goes by, the porosity decreases, the amount of CSH generated increases, and the matrix becomes denser. At 7 days, part of the RHA of R15S10 reacted with the surrounding CH, and the surface of the RHA was covered with needle-shaped CSH, but the surface of some large-volume RHA was still smooth and had not yet dissolved; at 28 days, we can find that the small-volume RHA gradually dissolved and disappeared, and a large amount of CSH gel filled the pores; some large-volume RHA particles also began to gradually dissolve, and filamentous substances appeared on the surface; the interface transition zone between the cement matrix and the aggregate became smooth and smooth, without obvious connection or bonding. The silicates formed by the dissolution of RHA were consumed by CH, and the reduction of CH in turn promoted the volcanic ash reaction of RHA; RHA absorbed calcium ions and reduced the calcium concentration, which was conducive to the dissolution of calcium-rich phases. The incorporation of RHA not only reduced the amount of CH formation, but also reduced the crystal size in the presence of new nucleation centers. The density of the cement matrix at 28 days was greater than that at 7 days, and the number of unhydrated particles decreased with the increase of curing time, which can correspond to the decrease in porosity and increase in compressive strength at 28 days.
[0154] Finally, the order of adding materials in the preparation process of cement mortar raw materials will also affect the performance of cement mortar products. The cement mortar products of Example B1 and Example B10 are as follows: Fig. 9 , Fig.10 As shown, Fig. 9 The sample marked M6 on the left is Example B10, and the sample marked M7 on the right is Example B1. Fig.10 The upper sample is Example B1, and the lower sample is Example B10. Combined with the porosity test results, it can be seen that if CSP is not first mixed with water to form a mixed slurry and release heat, the final cement mortar product will have large and numerous pores, and will have many cracks, and the density is very low, which is not conducive to the mechanical properties of the cement material.
[0155] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A gelling material, characterized in that: The composition comprises the following components in parts by weight: 5-20 parts of rice husk ash; 5-20 parts of calcined shell powder; 60-90 parts of cement; Wherein, the rice husk ash contains amorphous silicon dioxide.
2. The gelling material according to claim 1, characterized in that: The rice husk ash is prepared by calcining rice husk at 500-1000°C; And / or, the calcined shell powder is obtained by calcining shells at 800-1000°C and then grinding them.
3. The gelling material according to claim 1 or 2, characterized in that: The mass ratio of the amorphous silicon dioxide to the rice husk ash is 82% to 86%; And / or, the mass proportion of calcium oxide in the calcined shell powder is 95% to 98%.
4. The gelling material according to claim 1 or 2, characterized in that: The particle size of the rice husk ash is sieved through a 300-mesh sieve; And / or, the particle size of the calcined shell powder is sieved through a 325-mesh sieve.
5. The gelling material according to claim 1 or 2, characterized in that: The cement includes at least one of silicate cement and ordinary silicate cement.
6. A cement mortar, characterized in that: The cement mortar is prepared by mixing the cementitious material according to any one of claims 1 to 5 with water.
7. The cement mortar according to claim 6, characterized in that: The mass ratio of the gelling material to the water is 1:(0.18-0.35).
8. The cement mortar according to claim 6 or 7, characterized in that: The mixing process comprises the following steps: Firstly, the calcined shell powder and the water are prepared into a mixed slurry and heat is released; Then the rice husk ash, the mixed slurry and the cement are mixed.
9. The cement mortar according to claim 6 or 7, characterized in that: The raw materials for the mixing treatment also include at least one of aggregate, water reducing agent and defoaming agent.
10. A cement mortar product, characterized in that: The cement mortar product is obtained by curing the cement mortar as claimed in any one of claims 6 to 9 after molding.